Knowledge Management for Development Domains, Strategies and Technologies for Developing Countries - Osei-Bryson, Kweku-Muata.; Mansingh, Gunjan; Rao, Lila.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2014)
A number of developing countries, including small island states, have common problems that have affected their development and growth. Knowledge Management (KM) initiatives can be used to address some of these issues, but these developing countries need to understand what is needed to implement them, in order to improve economic conditions. While many of these countries have access to technologies that can be used to assist in knowledge management, relevant and low cost KM initiatives need to be considered in improving their existing KM processes. Sectors critical to the growth of these developing countries include health care, agriculture, disaster recovery management, small and medium-size enterprise development. Knowledge Management for Development: Domains, Strategies and Technologies for Developing Countries highlights the opportunities in these sectors and provides advice as to how these countries should go about understanding, building and adopting the relevant KM strategies and technologies. This book identifies appropriate technologies which should be considered to increase productivity within the identified sectors in the developing countries, and also sectors in which knowledge management initiatives can yield maximum value. It also considers the constraints of these territories, recommending appropriate technologies and strategies for KM initiatives. It provides advice on how these technologies should be adopted in these sectors of developing countries. Investing in these strategies should benefit these countries development and growth.
Chapter 1 Towards Understanding and Applying Knowledge Management and Knowledge Management Systems in Developing Countries: Some Conceptual Foundations -- Chapter 2 Towards a Community-Centered Knowledge Management Architecture for Disaster Management in Sub Saharan Africa -- Chapter 3 Managing Expert Knowledge to Assist in the Management of Coffee Pests and Diseases in Jamaica -- Chapter 4 Implementation of a Multiagent Supervisory System for an Agricultural Products Sourcing Network -- Chapter 5 Progressive Usage of Business and Spatial Intelligence for Decision Support in the Delivery of Educational Services in Developing Countries -- Chapter 6 Migrating MIS to KMS: A Case of Social Welfare Systems -- Chapter 7 Addressing a Knowledge Externality Schism in Public Policy in the English Speaking Caribbean -- Chapter 8 A Methodology for Developing High Quality Ontologies for Knowledge Management -- Chapter 9 The Role of Ontologies in Developing Knowledge Technologies -- Chapter 10 Knowledge Sharing in Repository Based KM Systems: A Study in the IT Services Enterprises in India -- Chapter 11 Ability to Share Knowledge of Doctors in Teaching Hospitals in Indonesia -- Chapter 12 Knowledge sharing in the Health Sector in Jamaica: The Barriers and the Enablers -- Chapter 13 The Ulwazi Programme: A Case Study in Community-focused Indigenous Knowledge Management -- Chapter 14 Knowledge Management for Programs on Information and Communications Technologies for Development (ICT4D) in South Africa.
Keywords: Economics; Information systems; Economics/Management Science; Emerging Markets/Globalization.; Information Systems and Communication Service; Economic Systems